(untitled) (CIPEEX, 2025)
Anatomical knowledge is fundamental to biomedical practice, especially in the field of imaging, also known as diagnostic imaging, where the correct interpretation of images depends on detailed knowledge of bodily structures. The skeletal system, because it is widely visualized in radiological examinations, becomes an essential focus in the technical and scientific training of professionals. The objective of this study was to analyze the relevance of anatomical knowledge, with an emphasis on the skeletal system, for the work of biomedical professionals in the field of imaging, considering legislation and the job market. This is a narrative review of the literature. The search was conducted in the SciELO, PubMed, and Google Scholar databases, using the descriptors “Human Anatomy,” “Skeletal System,” “Biomedicine,” and “Imaging,” combined by the Boolean operators AND and OR. Articles published between 2015 and 2025, in Portuguese or English, with free access and directly addressing biomedical practice or anatomical application in imaging were included. Duplicate works, those unrelated to the topic, or those focusing exclusively on other professions were excluded. The studies analyzed highlighted that anatomical knowledge is indispensable for qualified practice in Imaging, allowing the assessment of fractures, deformities, and malformations. Resolution No. 78/2002 of the Federal Council of Biomedicine (CFBM) regulates this practice and reinforces the need for technical training based on specialization with practical hours. The job market for biomedical professionals in this area has grown, requiring solid training and anatomical mastery. It is concluded that mastery of the skeletal system enhances the technical quality and insertion of biomedical professionals in Imaging.